Tinjauan Hukum Jual Beli Chip Game Online (Higgs Domino) Menurut Asas Kebebasan Berkontrak - Maulana, Rivaldo Inka (PT. Adikara Cipta Aksa, 2025)
Since the development of the internet, its use has become a means of activity for its users to carry out various activities, one of the most visible examples is business activities carried out online where it contributes to efficiency, fast, easy, and practical. Juridically, the agreement gives the widest freedom to the community to enter into agreements containing anything as long as it does not violate public order and decency. This is based on the principle of freedom of contract contained in article 1338 of the Civil Code. The law does not prohibit anyone from entering into an agreement, including its application in an online sale and purchase agreement based on the terms and conditions of the law. Transact buying and selling online. The government in this case is expected to provide a balanced position to sellers and consumers who hold online buying and selling transactions. This paper conducts normative legal research methods with a normative juridical approach, which refers to legal norms contained in laws and regulations. The method used is Library Research (literature research) by using and collecting data or materials for papers / seminars, laws and regulations and writings or articles sourced from the internet and interview methods using sources as research carried out so that there are no vacancies or something lacking in conducting tests. In the agreement there is an unfulfilled aspect, namely the non-halal clause in article 1320 of the Civil Code, from the transaction this agreement has violated the non-halal clause and is linked to the principle of freedom of contract explained in article 1338 of the Civil Code regarding freedom of contract, resulting in layered articles on both parties. Based on the research conducted, the results of transactions carried out by contractors, and producers are invalid, because they violate the provisions of the treaty law and the principle of freedom of contract.